21st century skills through film production in tertiary education: a transformative assessment in a literature and media course - Melissa Shamini Perry (Penerbit Universiti Kebangsaan Malaysia, 2018)
The 21st century lifestyle demands that individuals engage different communication modes and intelligences in every domain from learning, employment, communication and recreation and entertainment. In order to produce individuals that are competent and able to function competitively in the 21st century global field, tertiary education and assessments must move beyond traditional methods of essays, quizzes and exams that only test discipline related knowledge and memorization skills. Holistic, transformative assessments that can develop knowledge and skills and maximize an individual’s potential is important in creating competent and marketable graduates. This study discusses the development of 21st century skills through a short film production assessment in the Literature and the Media course taught at The National University of Malaysia. The core principles of formative assessments are used to guide the development, design and implementation of the short film production assessment. A distinctive aspect of the assessment is the inclusion of pitching and short film premiere event organization elements which were found to be very beneficial in helping students develop skills such as decision making, problem-solving and public speaking. The tasks involved in all three stages of the short film production assessment were found to be instrumental in developing fourteen 21st skills in students. Students’ reflections also provided an insight into the various skills developed through the assessment. This study reinforces the potential of filmmaking as a holistic and transformative assessment tool to equip tertiary students with the necessary skills to meet the demands of 21st century work and life environments.